The expression of melanopsin and clock genes in Xenopus laevis melanophores and their modulation by melatonin - Bluhm,A.P.C. (2012)
Vertebrates have a central clock and also several peripheral clocks. Light responses might result from the integration of light signals by these clocks. The dermal melanophores of Xenopus laevis have a photoreceptor molecule denominated melanopsin (OPN4x). The mechanisms of the circadian clock involve positive and negative feedback. We hypothesize that these dermal melanophores also present peripheral clock characteristics. Using quantitative PCR, we analyzed the pattern of temporal expression of Opn4x and the clock genes Per1, Per2, Bmal1, and Clock in these cells, subjected to a 14-h light:10-h dark (14L:10D) regime or constant darkness (DD). Also, in view of the physiological role of melatonin in the dermal melanophores of X. laevis, we determined whether melatonin modulates the expression of these clock genes. These genes show a time-dependent expression pattern when these cells are exposed to 14L:10D, which differs from the pattern observed under DD. Cells kept in DD for 5 days exhibited overall increased mRNA expression for Opn4x and Clock, and a lower expression for Per1, Per2, and Bmal1. When the cells were kept in DD for 5 days and treated with melatonin for 1 h, 24 h before extraction, the mRNA levels tended to decrease for Opn4x and Clock, did not change for Bmal1, and increased for Per1 and Per2 at different Zeitgeber times (ZT). Although these data are limited to one-day data collection, and therefore preliminary, we suggest that the dermal melanophores of X. laevis might have some characteristics of a peripheral clock, and that melatonin modulates, to a certain extent, melanopsin and clock gene expression.